Influence of vacuum on kinetic of low quality rapeseed oil amidation by aminoethylethanolamine - Kramarev, Sergiy; Husanov, Alisher (Eastern-European Journal of Enterprise Technologies, 2016)
The process of direct amidation of lowgrade canola oil with high free fatty acids content has been researched. Influence of different technological parameters on consumption of reagents and accumulation of reaction products have been established for the temperature of reaction 160 °С. Concentrations of esters, free fatty acids, alkylimidazolines and amine components have been determined during the reaction time. Application of vacuum during the amidation process has great influence on free fatty acids consumption as well as on alkylimidazoline formation. Effective rate constants have been calculated for reactions of conversion of free fatty acids and esters into amides with and without vacuum. It has been determined that effective rate constant of free fatty acids consumption under atmospheric pressure is three times lower than under vacuum 40–60 mm. Hg. as well as those for esters. Along with an increase in free fatty acids consumption, the speed of alkylimidazolines formation rapidly increases with vacuum applying. Such effect is explained by shifting of equilibrium in reactions of free fatty acids consumption and alkylimidazoline formation by removing of reaction water by vacuum. Formation of amides of fatty acids and alkylimidazolines confirmed by IRspectroscopy.